The Effect of Work-Life Balance, Job Autonomy, and Workload on Employee Performance at PT Rajawali Mas Prima - Adam, Firsa; Mardaleta, Mardaleta; Damrus, Damrus (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to investigate the effect of work-life balance, job autonomy, and workload on employee performance at PT Rajawali Mas Prima. The research approach used is descriptive quantitative with a sample of 49 employees. Sample collection used total sampling (census). Data were obtained through questionnaires and analyzed using multiple linear regression to test the relationship between variables. The results showed that worklife balance and job autonomy had a positive and significant effect on employee performance, while workload had a negative and significant effect. Simultaneously, the three independent variables had a significant effect on employee performance, with a coefficient of determination (R²) of 0.612, meaning that 61.2% of the variation in employee performance can be explained by these three factors. These findings emphasize the importance of creating a balance between work and personal life, providing freedom in carrying out tasks, and managing workload proportionally to improve employee performance and productivity in the company environment.